Association between the Immune Nutritional Index and Clinical Outcomes Following Percutaneous Coronary Intervention in ST-Elevation Myocardial Infarction: A Retrospective Cohort Study - Yuan, Rikang; Zhou, Yucheng; Li, Yimeng; Xu, Dongxia; Zong, Gangjun (International Journal of Angiology, 2025)
The prognosis and recovery of the patient post-percutaneous coronary intervention (PCI) procedure for myocardial infarction (MI) form a core clinical question. It is increasingly important to know the indices that can inform more effective organizational strategies in the prevention of cardiovascular adverse development among these groups of patients. The current study investigates the relationship between a novel index, Immune–Nutritional Index (INI), a product of albumin and lymphocyte, divided by neutrophils, and the incidence of a major adverse cardiovascular event (MACE) following PCI procedures. We conducted a retrospective analysis, from January 2020 to March 2024, on 367 patients with segment elevation (ST) myocardial infarction (STEMI) who were subjected to PCI at the 904th Hospital of the Joint Logistics Support Force. We computed the INI for each patient. The prediction of INI for both in-hospital and long-term MACE was discussed, and the area under the curve (AUC) was calculated. Three hundred and sixty-seven patients were categorized according to the best cutoff value of INI, and clinical characteristics were compared. Logistic and Cox regression analyses were performed to determine independent factors associated with in-hospital and long-term MACE, respectively. The Kaplan–Meier survival analysis determined patients' discharge survival outcomes. The AUC of INI for predicting in-hospital MACE in patients with STEMI was found to be 0.666, while for long-term MACE, it was found to be 0.748. A high INI was independently associated with reduced in-hospital MACE risk among patients with STEMI in multivariate logistic regression analysis (cutoff value 7.101; p < 7.101, odds ratio [OR] = 0.418, 95% confidence interval [CI]: 0.246–0.712). High INI significantly predicted long-term MACE during a follow-up period in patients with STEMI and was independently associated with it (cutoff value 9.752; p = 0.005, hazard ratio [HR] = 0.423, 95% CI: 0.232–0.770). INI is an important predictive index for MACE during hospitalization and long-term follow-up after PCI in STEMI patients.
Keywords: major adverse cardiovascular events; prevention; Immune–Nutritional Index; PCI; inflammation; acute coronary syndrome; cardiovascular disease